Analysis of Domestic Factors Affecting Outward Foreign Direct Investment in Brazil. Issue 1 (2nd January 2017) - Gondim, Igor Jordano Cassemiro; Morandier, Nadia; Dias, Ivan Rodrigo Rizzo; Couto, Cyro Augusto Pachicoski; Charotta, Teresa Cristina Alves
ABSTRACT: Developing markets have increasingly gained prominence in the world economy, but the domestic factors behind this success are not well established. This uncertainty may interfere with multinational expansion plans. In this article, we examine several macroeconomic and institutional factors affecting Brazilian outward foreign direct investment in 17 destination countries. We applied a pooled ordinary least squares regression over the 2001–2014 period. The findings suggest that macroeconomic factors are still statistically significant to explain investment abroad, but several institutional factors such as corruption have emerged, having a negative effect and political violence having a positive effect on Brazilian outward foreign direct investment.